Promjene u prikazu rata u novijem hrvatskom igranom filmu - stil, umjetnost, ideologija - Gilić, Nikica (Array, 2014)
Although recent Croatian cinema has not produced anything corresponding to the partisan genre in Yugoslavia (with very few exceptions, such as Stjepan Sabljak’s amateur film U okruženju), war has nevertheless been heavily represented in the films made since the break-up of Yugoslavia. Countering the dominant cinematic modus of the first half of the decade, Vinko Brešan's Kako je počeo rat na mom otoku was instrumental in broadening the scope of views on war that can be represented in Croatian film, as were some other Brešan’s films (particularly Svjedoci), while the films such as Kristijan Milić’s Živi i mrtvi, as well as Goran Dević and Zvonimir Jurić’s Crnci (preceded by Lukas Nola’s Nebo sateliti) reached impressive artistic peaks, at the same time pointing to the change in the Croatian society. The article also explains one possible explanation of the rise of quality of Croatian film in the 2000s: the genre film has become more prominent, which might be very significant if we subscribe to the notion that genre cinema can serve as a basis for a (national or any other) cinema.